F.l.t.r. sitting Pauline Masereel, Smit, Tchamba, standing in the centre Dabit, Masereel right. Paper with a drawing of Masereel
F.l.t.r. sitting Pauline Masereel, Smit, Tchamba, standing in the centre Dabit, Masereel right. Paper with a drawing of Masereel.